Pandemics and Urban Child Survival: Pulling Together in the Adoption Canoe - Johnson, Shelly (First Peoples Child & Family Review, 2015)
This article tells an intergenerational narrative about how historical pandemics and family adoptions stories can influence urban Indigenous custom adoption practices, policies, teaching and research. It uses the seven principles of Archibald’s (2008) storywork to link the importance of knowing our own family histories, and how those historical, cultural and current contexts can be a force to advocate, influence, research and teach for change. The “canoe” is a metaphor for re-conceptualizing adoption narratives, and emphasizes the idea of an “adoption journey” or a shared learning process.